Harry Truman and the struggle for racial justice - Shogan, Robert (University Press of Kansas, 2013)
The first full-scale, balanced account of President Truman's civil rights policies, tracing how the Missourian outgrew the bigotry of his Jackson County upbringing to become the president who integrated the military and lobbied for key civil rights legislation.